Contributions of the National School Feeding Program (PNAE) and the Food Acquisition Program (PAA) to strengthening family farming and promoting food security in Brazil (2015–2025): An integrative review (Research, Society and Development, 2025)
This study aims to analyze, through an integrative literature review, the contributions of public institutional purchasing policies—especially the National School Feeding Program (PNAE) and the Food Acquisition Program (PAA)—to the strengthening of family farming and the promotion of food security in Brazil between 2015 and 2025. The methodology consisted of selecting and critically analyzing 15 scientific articles from national and international databases, using inclusion criteria related to the theme, time frame, and academic relevance. The results show that PNAE and PAA have significant impacts on income generation, market access, and dietary diversification, particularly when associated with cooperatives and technical assistance. However, challenges such as bureaucratic barriers, budget discontinuity, and the low inclusion of women and traditional peoples were also identified. The North and Northeast regions are the most affected by structural and institutional inequalities in the implementation of these programs. It is concluded that despite the advances, the effectiveness of these public policies depends on the continuity of funding, the strengthening of local governance, and the expansion of access for vulnerable groups. Therefore, integrated actions and continuous investments are needed to ensure sustainable rural development and equitable food security in the country.